Activation of a Mitogen-Activated Protein Kinase Hog1 by DNA Damaging Agent Methyl Methanesulfonate in Yeast - Huang, Shan; Zhang, David; Weng, Fangli; Wang, Yuqi (Frontiers in Molecular Biosciences, 2020)
Hog1 is a mitogen-activated protein kinase in yeast that primarily regulates cellular responses to hyperosmolarity stress. In this study, we have examined the potential involvement of Hog1 in mediating cellular responses to DNA damaging agents. We find that treatment of yeast cells with DNA damaging agent methyl methanesulfonate (MMS) induces a marked and prolonged Hog1 activation. Distinct from stressors such as arsenite that activates Hog1 via inhibiting its phosphatases, activation of Hog1 by MMS is phosphatase-independent. Instead, MMS impairs a critical phosphor-relay process that normally keeps Hog1 in an inactive state. Functionally, MMS-activated Hog1 is not translocated to the nucleus to regulate gene expression but rather stays in the cytoplasm and regulates MMS-induced autophagy and cell adaptation to MMS stress. These findings reveal a new role of Hog1 in regulating MMS-induced cellular stress.